Rethinking Power Sector Reform : Positive Lessons for the Middle East and North Africa - Nguyen, Tu Chi; Rana, Anshul; Fernstrom, Erik Magnus; Foster, Vivien (World Bank, Washington, DC, 2020)
The need for greater efficiency and accountability in the power sector in the Middle East and North Africa has renewed pressure for reforms. A major new World Bank report, Rethinking Power Sector Reform in the Developing World (Foster and Rana 2020), examines how developing countries have attempted to reform their power sector and with what results. Some key lessons point the way forward.